The Drug–Drug Interaction Profile of Presatovir. (7th February 2018) - Xin, Yan; Weng, Winnie; Murray, Bernard P.; Eisenberg, Eugene J.; Chien, Jason W.; Ling, John; Silverman, Jeffrey A.
Abstract: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections in young children. Presatovir (previously GS‐5806) is a novel, orally administered RSV fusion inhibitor with a favorable safety profile and proven antiviral efficacy in preclinical and clinical studies. In vitro, presatovir is a substrate of the efflux transporters P‐glycoprotein (P‐gp) and breast cancer resistance protein (BCRP) and hepatic uptake transporters organic anion transporting polypeptide (OATP) 1B1 and OATP1B3 and is slowly metabolized by cytochrome P450 (CYP) 3A4 and CYP3A5. This study enrolled 64 healthy subjects to evaluate the effect of cyclosporine, a P‐gp, BCRP, and OATP1B1/1B3 inhibitor; rifampin, a strong CYP3A4 and P‐gp inducer; efavirenz, a moderate CYP3A4 inducer; and cobicistat, a potent CYP3A inhibitor, on presatovir pharmacokinetics. Presatovir plasma exposures (maximum observed plasma concentration [Cmax ] and area under the plasma concentration–time curve from time 0 extrapolated to infinity [AUCinf ]) were not affected by coadministration of cyclosporine, suggesting presatovir is not a sensitive substrate of P‐gp, BCRP, or OATP1B1/1B3. As expected, based on the role of CYP3A in presatovir metabolism, presatovir exposure was increased by cobicistat (122% in AUCinf ), and decreased by rifampin (40.3% in Cmax and 82.5% in AUCinf ) and efavirenz (55.7% in AUCinf ). These data support coadministration of presatovir with inhibitors of P‐gp, BCRP, OATP1B1/1B3, or CYP3A, but not with moderate or strong CYP3A4 inducers. Presatovir was well‐tolerated with the most common drug‐related adverse events of dizziness (n = 12) and somnolence (n = 4) reported during efavirenz treatment.